Entrainment of Perceptually Relevant Brain Oscillations by Non-Invasive Rhythmic Stimulation of the Human Brain - Thut, Gregor; Schyns, Philippe; Gross, Joachim (Frontiers in Psychology, 2011)
The notion of driving brain oscillations by directly stimulating neuronal elements with rhythmic stimulation protocols has become increasingly popular in research on brain rhythms. Induction of brain oscillations in a controlled and functionally meaningful way would likely prove highly beneficial for the study of brain oscillations, and their therapeutic control. We here review conventional and new non-invasive brain stimulation protocols as to their suitability for controlled intervention into human brain oscillations. We focus on one such type of intervention, the direct entrainment of brain oscillations by a periodic external drive. We review highlights of the literature on entraining brain rhythms linked to perception and attention, and point out controversies. Behaviourally, such entrainment seems to alter specific aspects of perception depending on the frequency of stimulation, informing models on the functional role of oscillatory activity. This indicates that human brain oscillations and function may be promoted in a controlled way by focal entrainment, with great potential for probing into brain oscillations and their causal role.